The Role of Teachers of Social Sciences as Role Models in Shaping Student Ethics at Smpn 1 Talun Cirebon - Malahayati, Tikah (Riviera Publishing, 2022)
The focus of this study is the probelm of studens’ ethics in communicating, which can be seen from the factors that support and inhibit social studies teachers in shaping students’ communication ethics. This study uses a qualitative type of research using a descriptive approach which will be described in depth from the results of exploration during the study. The subjects of this study were social studies teachers for class VIII-i, school principals, and students of class VIII-i. The data collection techniques used for this research are observation, data reduction, data display and conclusion drawing. The results showed that the communication ethics of class VIII-i students at SMPN 1 Talun Cirebon Regency was considered good, although it was not said to be optimal, but students were able to be flexsible with the conditions they faced. The role of the social studies teacher as a role model in shaping the ethics of class VIII-i students at SMPN 1 Talun Cirebon Regency has been carried out potimally as is the position of a teacher who carries out his rights and obligations as an educator, teaches, guides, gives moral messages and as a facilitator. This role has a positive impact on the teaching and learning process (KBM) and daily activity habits such as 5S (smile, greeting, greeting, politeness, courtesy). Factors that hinder students communication ethics are the detachment of supervision and influence from peers, geographical location and lack of cooperation between parents and teachers. The driving factors are language discipline in schools, encouragament and familiy factors that support children’s development to become better.